Access, Affordability, and Alternatives : Modern Infrastructure Services in Africa - Banerjee, Sudeshna; Wodon, Quentin; Diallo, Amadou; Pushak, Taras; Uddin, Helal; Tsimpo, Clarence; Foster, Vivien (World Bank, Washington, DC, 2013)
Africa lags well behind other developing regions in infrastructure access. The limited gains of the 1990s have not increased much in the 2000s. There is clear evidence that many countries are failing to expand services fast enough to keep ahead of rapid demographic growth and even faster urbanization. As a result, if present trends continue, Africa is likely to lag even further behind other developing regions, and universal access will be more than 50 years away in many countries. However, there is variation in performance across countries, even within the low and middle income brackets. A significant number of countries have succeeded in increasing the number of people who have access to water, electricity, and sanitation, by an annual average of 5-10 percent. Further investigation is warranted to explain what determines the superior performance of these countries.